2001
DOI: 10.1136/ard.60.5.467
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal cohort study of Finnish patients with primary Sjogren's syndrome: clinical, immunological, and epidemiological aspects

Abstract: 2) g/l) at the control visit were significantly (p<0.0001) lower than those at baseline. A similar change was observed in a subgroup of patients never treated with glucocorticosteroids or disease modifying antirheumatic drugs. Three non-Hodgkin's lymphomas were diagnosed (standardised incidence ratio 13; 95% confidence interval 2.7 to 38). In a logistic regression model, the patients with pSS with subsequent lymphoma were found to have higher baseline levels of serum 2 microglobulin than the others (odds ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 35 publications
5
78
1
5
Order By: Relevance
“…The total observation time was 3,648 patient-years at risk. Our results confirm the findings of earlier smaller studies (8)(9)(10) and the recently published large retrospective study from 2 university hospital patient cohorts in Greece (11), i.e., a statistically significant increase in all-cause mortality among patients with primary SS could not be documented. We used the new AECC for assessing whether patients with autoimmune disease have worse long-term outcome than those with sicca symptoms without detectable autoimmune disturbances or more nonspecific immune activation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The total observation time was 3,648 patient-years at risk. Our results confirm the findings of earlier smaller studies (8)(9)(10) and the recently published large retrospective study from 2 university hospital patient cohorts in Greece (11), i.e., a statistically significant increase in all-cause mortality among patients with primary SS could not be documented. We used the new AECC for assessing whether patients with autoimmune disease have worse long-term outcome than those with sicca symptoms without detectable autoimmune disturbances or more nonspecific immune activation.…”
Section: Discussionsupporting
confidence: 91%
“…Martens et al (8) studied 50 patients with primary SS at the Mayo Clinic in Rochester, Minnesota and reported survival of these patients to be comparable with that of the healthy population. In a recent study in Finland, the standardized mortality ratio (SMR) in 110 patients with primary SS was 1.2; 70% of these patients had classic focal sialadenitis (focus score Ն1) seen on salivary gland biopsy (9). In a study of 261 Greek patients, Skopouli et al found an SMR of 2.07 (95% confidence interval [95% CI] 1.03-3.71), with a low C4 level at diagnosis as a predictor variable for death (10).…”
mentioning
confidence: 99%
“…Only consecutive patients with primary SS who fulfilled the American-European Consensus Group criteria were recruited, and the study population was representative of the disease with regard to clinical, biologic, and immunologic features (26).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, Hashimoto's thyroiditis (HT) and Sjögren's syndrome (SS) are the best examples with increased relative risks of 3-67 43,44 and 9-44, 43,[45][46][47][48] respectively to develop extranodal marginal zone B-cell lymphomas (MZBCLs). Moreover, for SS patients a 9-fold increased risk of obtaining a diffuse large B-cell lymphoma (DLBCL) has been reported.…”
Section: Auto-immune Inflammatory Conditions Associated With B-cell Lmentioning
confidence: 99%